The Interagency Relationship Between the Personnel Department and the Organization & Management Unit in the Arab Republic of Egypt - El Sebai, Mohamed M Rifaat (AUC Knowledge Fountain, 1972)
The development of the personal department in the Arab of Egypt is slow.